Using DNA barcodes to identify forensically important species of Diptera in Espírito Santo State, Brazil - Oliveira,Pablo Viana (2017)
ABSTRACT Accurate insect specimen identification is usually a crucial first step in a forensic entomological analysis. It is traditionally done by morphological classification using identification keys. However, due to sensibility limitations in the identification of animal species based only on their morphology, new methods have been developed, including species identification by DNA barcodes. The objective of this study was to identify forensically important species of Diptera in Espirito Santo state using DNA barcodes. For this, adult flies were collected in Espirito Santo, Southeast Region of Brazil. After DNA extraction, COI gene was amplified and sequenced. All sequences were matched to BOLD platform and alternatively to GenBank MegaBLAST. As result, 281 adult flies were collected and identified morphologically. From these, 36% of samples were classified as Calliphoridae, 34% of Muscidae and 30% of Sarcophagidae. Approximately 10% of all collected samples were analyzes by DNA. It was possible to identify only 35.7% of tested samples, probably due to lack of samples deposited in databases. Therefore, more efforts should be made to deposit a greater variety of dipterous in databases to allow the use of this technique in forensic routine, especially in BOLD.